Characterization of Mechanical Properties and Microstructure of Aluminium Alloy-SiC Composites. (2015) - Rana, R.S.; Purohit, Rajesh; Soni, V.K.; Das, S.
Abstract: In recent years aluminium alloys are widely used in automotive industries due to light weight, good formability, high corrosion resistance and high electrical and thermal conductivity. However, the poor mechanical and tribological properties of pure aluminium alloys limit its wider range of applications. The mechanical properties can be improved by addition of ceramic particles like SiC, Al2 O3 etc. AMCs combine the metallic properties of matrix alloys (ductility and toughness) with ceramic properties of reinforcements (high strength and high modulus) and lead to higher strength in tension and compression and higher service temperature capabilities. In this study, AA 5083 alloy-SiC composites have been fabricated by Ultrasonic assisted Stir casting. Different weight % of SiC (3, 5, 8 and 10 wt %) were used for synthesis of composites. SEM micrographs show uniform distribution of SiC particles with agglomeration at some places. The application of ultrasonic vibration on the composite during melting not only refined the grain structure of the matrix, but also improved the distribution of nano-sized reinforcement.